Silica bodies and their systematic implications at the subfamily level in Podostemaceae - Filipe Gomes Cardoso Machado da Costa; Claudia Petean Bove; Rosani do Carmo Oliveira Arruda; C. Thomas Philbrick (Rodriguésia)
Abstract Podostemaceae is a family of eudicotyledonous rheophytes with unique morphology, sometimes resembling algae, lichens or bryophytes. This study evaluates the taxonomic value of silica-body morphology (presence, location, size, shape, ornamentation) in species representing the three subfamilies: Tristicha trifaria (Bory ex Willd.) Spreng. (Tristichoideae), Weddellina squamulosa Tul. (Weddellinoideae) and Diamantina lombardii Novelo, C.T. Philbrick & Irgang (Podostemoideae). T. trifaria and D. lombardii have silica bodies in stems and leaves. In contrast, W. squamulosa exhibits silica bodies only in the scale-like leaves. The morphology of these bodies is unique to each species. The results denote the taxonomic usefulness of silica characteristics and a need for a more complete study of silica bodies throughout the family.